2017
DOI: 10.18632/oncotarget.16834
|View full text |Cite
|
Sign up to set email alerts
|

MiR-199a-3p enhances cisplatin sensitivity of cholangiocarcinoma cells by inhibiting mTOR signaling pathway and expression of MDR1

Abstract: Several studies have reported reduced miRNA-199a-3p (miR-199a-3p) in different human malignancies, however, little is known about miR-199a-3p in cholangiocarcinoma cells. In this study, we demonstrate the essential role and mechanism of miR-199a-3p in regulating cisplatin sensitivity in cholangiocarcinoma cell lines. Using a CCK-8 cell counting assay we found that expression of miR-199a-3p was positively correlated with cisplatin sensitivity in cholangiocarcinoma cell lines. MiR-199a-3p overexpression could de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…The overall survival prediction of muscle‐invasive bladder cancer patients after radical cystectomy could be improved by miR‐199a‐3p . In cholangiocarcinoma cells, miR‐199a‐3p enhances cisplatin sensitivity by inhibiting mTOR signalling pathway and expression of MDR1 . miR‐199a‐3p also suppresses proliferation and invasion of prostate cancer cells by targeting Smad1 .…”
Section: Discussionmentioning
confidence: 99%
“…The overall survival prediction of muscle‐invasive bladder cancer patients after radical cystectomy could be improved by miR‐199a‐3p . In cholangiocarcinoma cells, miR‐199a‐3p enhances cisplatin sensitivity by inhibiting mTOR signalling pathway and expression of MDR1 . miR‐199a‐3p also suppresses proliferation and invasion of prostate cancer cells by targeting Smad1 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Yang et al reported that the inhibition of miR-199a-3p reduced cisplatin-induced cell apoptosis and inhibited caspase-3 activity [40]. mTOR is the target gene of miR-199a [76], regulating cell survival, proliferation, migration, and apoptosis. In addition, miR-199a-3p increased TGF-β1-induced renal fibrosis via silencing of SOCS7 and STAT3 [41].…”
Section: Versatile Msc-evs-derived Mirnas Modulate Renal Injury and Hmentioning
confidence: 99%
“…Breast cancer Over-expression of these miRNAs re-sensitizes the drug-resistant cells to doxorubicin [45] miR-199a-3p MTOR Cholangiocarcinoma Reconstitution of miR-199a-3p increases growth inhibition rate and apoptosis induced by cisplatin [39] miR-210-3p ABCC5 Pancreatic cancer Elevated miR-210-3p levels improve the overall cytotoxicity of gemcitabine [26] miR-218-5p PRKCE Gallbladder cancer Elevated miR-218-5p levels potentiate gemcitabine-mediated cell death and growth inhibition [38] miR-223-3p ABCB1 Hepatocellular carcinoma Down-regulation of miR-223-3p confers resistance to doxorubicin [18] miR-326 ABCC1 Hepatocellular carcinoma Over-expression of miR-326 leads to elevated cytotoxicity of doxorubicin [23] miR-328-3p ABCG2 Breast cancer Over-expression of miR-328-3p augments the sensitivity of drug-resistant cells to mitoxantrone [29] miR-491-3p ABCB1, SP3 Hepatocellular carcinoma Down-regulation of miR-491-3p decreases the sensitivity to doxorubicin and vinblastin [19] miR-495-3p ABCB1, UBE2C Ovarian cancer, Gastric cancer, Lung cancer…”
Section: Spin1mentioning
confidence: 99%
“…There is another possibility that miR-506-3p regulates ABCB1 expression by targeting the enhancer of zeste homolog 2 (EZH2), which is a possible transcription regulator of ABCB1 [36,37]. In addition, a decrease in ABCB1 expression can be mediated by miR-199a-3p and miR-218-5p via regulating mTOR and protein kinase C epsilon (PRKCE, also known as PKCε), respectively [38,39]. Since both mTOR and PKCε activate the signal transducer and activator of transcription 3 (STAT3), a transcription factor of ABCB1 [40][41][42], it is feasible that miR-199a-3p and miR-218-5p could downregulate ABCB1 levels through a common mediator.…”
Section: Introductionmentioning
confidence: 99%